Ghrelin is involved in the paracrine communication between neurons and glial cells. Issue 9 (19th June 2013) - Avau, B.; De, B.; Thijs, T.; Geuzens, A.; Tack, J.; Vanden Berghe, P.; Depoortere, I.
Abstract Background Ghrelin is the only known peripherally active orexigenic hormone produced by the stomach that activates vagal afferents to stimulate food intake and to accelerate gastric emptying. Vagal sensory neurons within the nodose ganglia are surrounded by glial cells, which are able to receive and transmit chemical signals. We aimed to investigate whether ghrelin activates or influences the interaction between both types of cells. The effect of ghrelin was compared with that of leptin and cholecystokinin (CCK). Methods Cultures of rat nodose ganglia were characterized by immunohistochemistry and the functional effects of peptides, neurotransmitters, and pharmacological blockers were measured by Ca2+ imaging using Fluo‐4‐AM as an indicator. Key Results Neurons responded to KCl and were immunoreactive for PGP‐9.5 whereas glial cells responded to lysophosphatidic acid and had the typical SOX‐10‐positive nuclear staining. Neurons were only responsive to CCK (31 ± 5%) whereas glial cells responded equally to the applied stimuli: ghrelin (27 ± 2%), leptin (21 ± 2%), and CCK (30 ± 2%). In contrast, neurons stained more intensively for the ghrelin receptor than glial cells. ATP induced [Ca2+]i rises in 90% of the neurons whereas ACh and the NO donor, SIN‐1, mainly induced [Ca2+]i changes in glial cells (41 and 51%, respectively). The percentage of ghrelin‐responsive glial cells was not affected by pretreatment with suramin, atropine, hexamethonium or 1400 W, but was reduced by l‐NAME and by tetrodotoxin. Neurons were shown to be immunoreactive for neuronal NO‐synthase (nNOS). Conclusions & Inferences Our data show that ghrelin induces Ca2+ signaling in glial cells of the nodose ganglion via the release of NO originating from the neurons.